PERUBAHAN SERTIPIKAT HAK GUNA BANGUNAN MENJADI HAK MILIK ATAS TANAH - Rohim, Abdur; Rudi Cahyono (STIH Zainul Hasan Kraksaan Kraksaan, 2023)
Abstract In Probolinggo Regency, there are many lands that were built to be residential houses, one of which is housing with the status of Building Use Rights (HGB). This research is to find out how the implementation of the change in Rights from Building Use Rights to Ownership Rights based on the Basic Agrarian Law (LoGA) Number 5 of 1960 This research uses the Juridical Empirical method. The sources used are Primary Data Sources which are data sources to obtain primary data by conducting field research by conducting interviews and direct consultations with related parties and secondary data sources in the form of writing obtained by conducting library research, whether in the form of books. general, as well as laws and regulations in order to obtain a theoretical basis. Based on the data analysis carried out, it was concluded that in the process of implementing the change of Building Use Rights into Ownership Rights by a legal entity / developer in registering the improvement process at the Probolinggo Regency Land Office requires 12 (twelve) stages within a period of 7 (seven) days based on Regulation of the Head of the National Land Agency of the Republic of Indonesia Number 1 of 2010 concerning Standards for Land Services and Regulations (SPOPP), so that the certificate changes to the status of Property Rights. Keywords: Changes, use rights, buildings, become property rights